Supramolecular halogen bond passivation of organic-inorganic halide perovskite solar cells. - Abate, A; Saliba, M; Hollman, D; Stranks, S; Wojciechowski, K; Avolio, R; Grancini, G; Petrozza, A; Snaith, H (American Chemical Society, 2014)
Organic-inorganic halide perovskites, such as CH3NH3PbX3 (X = I(-), Br(-), Cl(-)), are attracting growing interest to prepare low-cost solar cells that are capable of converting sunlight to electricity at the highest efficiencies. Despite negligible effort on enhancing materials' purity or passivation of surfaces, high efficiencies have already been achieved. Here, we show that trap states at the perovskite surface generate charge accumulation and consequent recombination losses in working solar cells. We identify that undercoordinated iodine ions within the perovskite structure are responsible and make use of supramolecular halogen bond complexation to successfully passivate these sites. Following this strategy, we demonstrate solar cells with maximum power conversion efficiency of 15.7% and stable power output over 15% under constant 0.81 V forward bias in simulated full sunlight. The surface passivation introduces an important direction for future progress in perovskite solar cells.